Sicily represents the Italian reservoir of chloroplast DNA diversity of Quercus ilex L. (Fagaceae) - Fineschi, Silvia; Cozzolino, Salvatore; Migliaccio, Marianna; Musacchio, Aldo; Innocenti, Michela; Vendramin, Giovanni G. (Ann. For. Sci., 2005)
Chloroplast DNA polymorphism was analysed in forty-four Italian holm oak populations. Results obtained with different markers (PCR-RFLP and SSR) were congruent, showing a clear geographic structure of genetic diversity and high value of genetic differentiation (Gst = 0.80). By combining PCR-RFLP and SSR, eight haplotypes were identified in Italy, six of them in Sicily. Most populations were fixed for one haplotype. Some populations from the extreme West Mediterranean (Morocco) and the extreme East Mediterranean areas (Crete) were interpreted as reproductively isolated populations because they had completely different haplotypes. These results strongly support the hypothesis of glacial refugia existing in southern Italy, and underline the high conservation value of natural tree populations in Sicily, in which most diversity was detected.
Keywords: genetic differentiation; PCR-RFLP; Quercus ilex; SSR